Primary intracranial sarcomas: a clinicopathological investigation - Cai, Yu-Xiang; Liu, Jin-Sheng; Xu, Jian; He, Yong-Ze; Zhang, Huai-Nian; Tian, Su-Fang; Li, Zhi-Qiang (Frontiers in Oncology, 2023)
Abstract Background: The purpose of this study is to present a series of primary intracranial sarcomas (PIS), a rare type of tumor of the central nervous system, in order to improve our understanding of the disease. These tumors are heterogeneous and prone to recurrence after resection, exhibiting a high mortality rate. As PIS has yet to be understood and studied on a large scale, it is vital for further evaluation and research. Methods: Our study included 14 cases of PIS. The patients' clinical, pathological, and imaging features were retrospectively analyzed. Additionally, targeted DNA next-generation sequencing (NGS) was applied for the 481-gene panel to detect gene mutations. Results: The average age for PIS patients was 31.4 years. Headache (7, 50.0%) was the most common symptom leading to the hospital visit. Twelve cases had PIS located in the supratentorial area and two in the cerebellopontine angle region. The maximum tumor diameter ranged from 19.0 mm to 130.0 mm, with an average diameter of 50.3 mm. Pathological types of tumors were heterogeneous, with chondrosarcoma being the most common, followed by fibrosarcoma. Eight of the 10 PIS cases that underwent MRI scanning showed gadolinium enhancement; 7 of these cases were heterogeneous, and 1 of them was garland-like. Targeted sequencing was performed in two cases and identified mutations in genes such as NRAS, PIK3CA, BAP1, KDR, BLM, PBRM1, TOP2A, DUSP2, and CNV deletions of SMARCB1. Additionally, the SH3BP5::RAF1 fusion gene was also detected. Of the 14 patients, 9 underwent a gross total resection (GTR), and 5 chose subtotal resection. Patients who underwent GTR displayed a trend toward superior survival. Among the 11 patients with available follow-up information, one had developed lung metastases, three had died, and eight were alive. Conclusion: PIS is extremely rare compared to extracranial soft sarcomas. The most common histological type of intracranial sarcoma (IS) is chondrosarcoma. Patients who underwent GTR of these lesions showed improved survival rates. Recent advancements in NGS aided in the identification of diagnostic and therapeutic PIS-relevant targets.